2021
DOI: 10.1002/adfm.202009580
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Synthesis of Various Electrocatalysts on Ni Foam Using a Universal and Facile Induction Heating Method for Efficient Water Splitting

Abstract: Electrocatalytic water splitting for the production of hydrogen proves to be effective and available. In general, the thermal radiation synthesis usually involves a slow heating and cooling process. Here, a high‐frequency induction heating (IH) is employed to rapidly prepare various self‐supported electrocatalysts grown on Ni foam (NF) in liquid‐ and gas‐phase within 1–3 min. The NF not only serves as an in situ heating medium, but also as a growth substrate. The as‐synthesized Ni nanoparticles anchored on MoO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(42 citation statements)
references
References 47 publications
1
39
0
Order By: Relevance
“…Besides the characteristic peaks of CoSe 2 , the other peaks can be assigned to the planes of CoNi LDH (JCPDS 33‐0429). [ 30,31 ] Simultaneously, the same characteristic peaks are observed in the XRD pattern of V‐CoSe 2 @CoNi LDH HNA (Figure S8, Supporting Information). The results demonstrate that CoSe 2 and CoNi LDH are successfully integrated.…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…Besides the characteristic peaks of CoSe 2 , the other peaks can be assigned to the planes of CoNi LDH (JCPDS 33‐0429). [ 30,31 ] Simultaneously, the same characteristic peaks are observed in the XRD pattern of V‐CoSe 2 @CoNi LDH HNA (Figure S8, Supporting Information). The results demonstrate that CoSe 2 and CoNi LDH are successfully integrated.…”
Section: Resultssupporting
confidence: 61%
“…Besides the characteristic peaks of CoSe 2 , the other peaks can be assigned to the planes of CoNi LDH (JCPDS 33-0429). [30,31] Simultaneously, the 2b), corresponding to Co 2p 3/2 and Co 2p 1/2 of Co-Se bond, [32,33] while the peaks at 779.1 and 794.3 eV of Co 2p 3/2 and Co 2p 1/2 belong to Co-O bond for CoNi LDH. Obviously, the binding energies of Co 2p 3/2 and Co 2p 1/2 for B-CoSe 2 @CoNi LDH are higher than that of B-CoSe 2 , but lower than that of CoNi LDH.…”
Section: Resultsmentioning
confidence: 88%
“…[ 3 ] High‐efficiency and ideal catalysts often required lower HER overpotential to maintain large current density. [ 4 ] A large number of studies had shown that precious metal‐based catalysts (i.e., Pt, RuO 2 , and IrO 2 ) possessed great activity in hydrogen production. Nevertheless, its scarcity and high price conformed to its limitation in large‐scale industrial productions.…”
Section: Introductionmentioning
confidence: 99%
“…By utilizing the high-frequency induction heating (IH), Xiong et al was synthesized NiFe layered double hydroxide loaded on Ni foam (NiFe LDH / NF-IH), which had a certain number of defects and provided excellent OER performance with an overpotential of 246 mV (10 mA/cm 2 ). [63]…”
Section: Constructed Defectsmentioning
confidence: 99%